Activation of the Si-B interelement bond related to catalysis - Feng, Jian-Jun; Mao, Wenbin; Zhang, Liangliang; Oestreich, Martin (Chemical Society reviews, 2021)
Si-B reagents, namely silylboronic esters and silylboranes, have become increasingly attractive as versatile reagents to introduce silicon and boron atoms into organic frameworks. Diverse transformations through transition-metal-catalysed or transition-metal-free Si-B bond activation have become available. This Review summarises the recent developments in the now broad field of Si-B chemistry and covers the literature from the last seven years as an update of our review on the same topic published in early 2013 (M. Oestreich, E. Hartmann and M. Mewald, Chem. Rev ., 2013, 113 , 402-441). It mainly focuses on new applications of Si-B reagents but new methods of their preparation and, where relevant, reaction mechanisms are also discussed. Covering the past seven years, this review comprehensively summarises the latest progress in the preparation and application of Si-B reagents, including the discussion of relevant reaction mechanisms.